Trend in percutaneous coronary intervention volume following the COURAGE and BARI-2D trials: Insight from over 8.1 million percutaneous coronary interventions. (15th March 2015) - Bangalore, Sripal; Gupta, Navdeep; Généreux, Philippe; Guo, Yu; Pancholy, Samir; Feit, Frederick
Abstract: Background: COURAGE and BARI-2D have questioned the utility of routine revascularization for the prevention of cardiovascular events in patients with stable ischemic heart disease (SIHD). On the other end of the spectrum, a routine invasive strategy in patients with acute coronary syndrome (ACS) is superior to a conservative strategy. The impact of the above trials on the trend in percutaneous coronary intervention (PCI) volume for SIHD and ACS is not known. Methods: Data from the 2001–2011 Nationwide Inpatient Sample for discharges with PCI were used. The trend in PCI volume over time was analyzed, especially in relation to the COURAGE (2007) and the BARI-2D (2009) trials. Age and gender adjusted PCI rates were calculated using direct standardization method. Results: Among the 8, 150, 764 PCI procedures, there was a steady increase in PCI volumes until the publication of the COURAGE/BARI-2D trials after which the volume decreased. Compared to the peak volume of 909, 331 in 2006, PCI volume declined by 38% to 562, 036 in 2011 (P < 0.0001); driven by a 60% decrease in PCI for SIHD from 409, 199 in 2006 to 160, 707 in 2011 (P < 0.0001). Moreover, there was a 20% decrease in PCI for ACS from 500, 132 in 2006 to 401, 330 in 2011 (P < 0.0001) driven by a significant decrease in PCI for unstable angina. Results were similar in diabetics with a decline in the volume after BARI-2D trial, although the decline was less dramatic. Conclusion: The 11-year trend indicates a substantial impact of COURAGE/BARI-2D on SIHD PCI volumes with an unintended consequence of lower PCI volumes for ACS.